Spatial Strategies Used by Students With Visual Impairments to Solve Questions of Spatial Visualization. (September 2021) - Arslan, Ayşenur; Kayhan Altay, Mesture
Introduction: This study examines the spatial abilities of middle school students with visual impairments (i.e., blindness and low vision) in the context of spatial visualization. The study also aims to examine the strategies used by such students in solving questions requiring spatial ability.Methods: Participants comprised eight students with visual impairments attending the 8th grade of a school in Ankara, Turkey, which teaches students with visual impairments. The data collection tool is composed of eight questions under the guidance of the definition for spatial visualization. Question types belonging to the spatial visualization subcomponent were organized in four topics: 2D rotation, 3D rotation, paper folding, and cube folding.Results: It was observed that students with visual impairments used mental rotation and key feature strategies for 2D rotation questions. They used the key feature strategy for 3D rotation questions and the mental manipulation strategy for cube folding and paper folding questions.Discussion: In this study, it was identified that strategies used by students with visual impairments show similarities with spatial strategies defined in the literature as used by students without visual impairments. Of all the other types of questions, the most successful question of students with visual impairments is the paper folding question.Implications for practitioners: The results of this article can help teachers become aware of the kind of difficulties that students with visual impairments encounter when they try to solve questions that require spatial ability.